Management Consulting for Technological Modernization and Industry of the Future - Gitelman, Leonid Davidovich; Kozhevnikov, Mikhail Viktorovich (Economy of Regions, 2017)
The article presents the results of the authors' study based on the hypothesis that addressing the multidimensional highly complex tasks of technological modernization and new industry against the background of a wave of breakthrough innovations is only possible within the framework of proactive management. Its methodological, instrumental and competence basis results from «smart» partnership of regional science, education, and business. In this case, the management consulting of a new type, being fundamentally different from the traditional one, plays the role of the partnership coordinator. These differences are expressed in specific intellectual logistics and organizational architecture of consulting projects, close connection to universities, innovation centres and various research structures of the region as well as the high specialization, which is reached by the involvement of the virtual teams of cross-disciplinary experts in the developments, the flexible products designed on the basis of the modular principle. In this regard, the study presents a number of new scientific results proving the hypothesis. The paper substantiates the approach to the organization and methodology of consulting activities for complex, rapidly developing systems which requires expanding the range of competencies and scope of the interaction of various actors - carriers of interdisciplinary knowledge. In accordance with this approach, the authors introduce the concept of integratory consulting for advanced development that offers a package of intellectual services for addressing challenges of the future. We have developed the methodology of the integrated system of research, consultations, training and transforming action that makes it possible to generate pre-emptive actions amid crisis, risk and threats. The article has proposed and tested an organizational mechanism of cooperation between parties (science, education, business) involved in smart partnership and consulting. The mechanism employs a cutting-edge forward-looking business model that meets contemporary requirements and tasks.